(untitled) (Proceeding of the International Conference on Arts and Humanities, 2018)
Indian society is been stratified based on religion, caste, education, class, language and it interconnects with gender too. Social exclusion based on these stratifications occurs in the society largely. Mostly, Indians accept, respect and tolerate a wide range of differences in cultures, religions, languages, and customs. Despite Indian society’s general ambiance of acceptance and tolerance, there appears to be limited public knowledge and understanding of same-sex sexual orientation and people whose gender identity and expression are dissimilar with their biological sex. Majority of the people think of gender as a kind of inalienable property of individuals, as something we either are or have. Hence, when gender non-conformity is evident in a person, exclusion of that person is being practiced even in their family of orientation. Although transgender community has recognition in Hindu society to some extent, in contemporary context, their gender non-conformity makes them socially excluded. Therefore, this article will analyze and discuss on social exclusion of transgender community with special reference to Tamil Nadu. This article aims to: Highlight the extent of social exclusion and corresponding problems faced by transgender community of Tamil Nadu. Address the challenges faced by the transgender community of Tamil Nadu. Identify the solutions to the problems and challenges faced by the transgender community. The article explores contemporary research studies on transgender community, for instance, while transsexual studies was focused mostly on male-to-female transsexual perspective, this article also includes female-to-male transsexual and transgender community. This article is complied with case studies as primary sources and the secondary data available in the field of sociology along with some of the inputs from other disciplines such as history, economics and psychology. This article also reveals current trends of sociological inquiry in the area of transgender community in Tamil Nadu as a discussion of sociology’s possible contributions towards transgender community.